Composite parts
By dispersing conductive materials in an inorganic matrix, the stability of metal hydroxyoxides is used to solve the preparation limitations of high temperature and inactive atmosphere in the prior art, and the preparation of conductive ceramic composite materials by low-temperature sintering is realized , improves the heat resistance and stability of the material.
Patent Information
- Application Number
- CN202180092853.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-02-05
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-02-05
AI Technical Summary
The prior art requires firing under high temperature and inactive atmosphere when manufacturing conductive ceramic composite materials, which limits material selection and process flexibility, and conducting materials with low heat resistance are difficult to prevent oxidation and decomposition.
The composite component composed of metal hydroxyoxides is used to partially disperse conductive materials in the inorganic matrix, and the stability of the metal hydroxyoxide is used to suppress the oxidation of the conductive materials, thereby realizing the preparation of the low-temperature sintering method.
It is realized that the conductive composite material is manufactured without high temperature and inactive atmosphere, which improves the heat resistance and stability of the material, reduces the production cost, and suppresses the oxidation and deterioration of the conductive material.
Smart Images

Figure CN116830216B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite component. Background Art
[0002] In recent years, there has been an increasing demand for ceramics that exhibit relatively high electrical conductivity in the electrical and electronic fields. Therefore, research on imparting electrical conductivity to ceramics has been actively conducted.
[0003] Patent Document 1 discloses an alumina sintered body, a silicon nitride sintered body, and an aluminum nitride sintered body imparted with conductivity. Specifically, a conductive composite ceramic is disclosed, which has the following structure: conductive ceramic particles formed of any one or more of TiC, TiN, WC, TaC, MoC, NbC, and VC are finely dispersed in a non-conductive ceramic formed of any one or more of Al2O3, Si3N4, and AlN.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent No. 5096720 Summary of the invention
[0007] Here, in the sintering process of Patent Document 1, in order to prevent the oxidative decomposition of the conductive ceramic particles, the molded body is heated at 1300 to 2000° C. in an inert gas atmosphere. That is, in the manufacturing method of conductive ceramics using the conventional sintering method, in order to prevent the oxidative decomposition of the conductive material, it is necessary to perform sintering in an inert atmosphere. In addition, in the conventional sintering method, for example, the molded body needs to be heated to 1000° C. or more, so there is a problem that only conductive materials with high heat resistance can be used.
[0008] The present invention has been made in view of the technical problems of the prior art. Another object of the present invention is to provide a composite component that does not require sintering in a high temperature and in an inert atmosphere during production and that can impart conductivity even when a conductive material with low heat resistance is used.
[0009] In order to solve the above technical problems, the composite component involved in the embodiment of the present invention comprises: an inorganic matrix part, which is composed of an inorganic substance containing a metal oxyhydroxide (also called a metal oxide hydroxide); and a conductive material part, which exists in a state of being dispersed inside the inorganic matrix part and has conductivity. In addition, in the composite component, the porosity of the cross section of the inorganic matrix part is less than 20%. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 It is a cross-sectional view schematically showing an example of the composite component according to the present embodiment.
[0011] Figure 2 This is a graph showing the X-ray diffraction pattern of the hydraulic alumina used in Example 1, and the patterns of boehmite (AlOOH) and gibbsite (Al(OH) 3 ) registered in ICSD.
[0012] Figure 3 It is a schematic diagram for explaining a method for measuring the volume resistivity of test samples of Examples and Comparative Examples.
[0013] Figure 4 This is a graph showing the relationship between the volume resistivity and the volume ratio of metal particles of the test samples of Examples and Comparative Examples.
[0014] Figure 5 The scanning electron microscope photographs show the results of observing the cross section of the test sample of Example 2 at a magnification of 3000 times. (a) shows a secondary electron image of the cross section of the test sample, and (b) shows a reflected electron image of the cross section of the test sample.
[0015] Figure 6 The scanning electron microscope photographs show the results of observing the cross section of the test sample of Example 1 at a magnification of 5000 times. (a) is a diagram showing a secondary electron image of the cross section of the test sample, and (b) is a diagram showing data after the secondary electron image is binarized.
[0016] Figure 7 The scanning electron microscope photographs show the results of observing the cross section of the test sample of Example 1 at a magnification of 20,000 times. (a) is a diagram showing a secondary electron image of the cross section of the test sample, and (b) is a diagram showing data after the secondary electron image is binarized.
[0017] Figure 8 The scanning electron microscope photographs show the results of observing the cross section of the test sample of Example 2 at a magnification of 5000 times. (a) is a diagram showing a secondary electron image of the cross section of the test sample, and (b) is a diagram showing data after the secondary electron image is binarized.
[0018] Fig. 9 The scanning electron microscope photographs show the results of observing the cross section of the test sample of Example 2 at a magnification of 20,000 times. (a) is a diagram showing a secondary electron image of the cross section of the test sample, and (b) is a diagram showing data after the secondary electron image is binarized.
[0019] Fig.10 It is a graph showing the X-ray diffraction pattern of the test sample of the reference example and the X-ray diffraction patterns of boehmite and gibbsite registered in ICSD. DETAILED DESCRIPTION
[0020] Hereinafter, a composite component and a method for manufacturing the composite component according to the present embodiment will be described with reference to the drawings. It should be noted that, for the sake of convenience of description, the dimensional ratios in the drawings may be exaggerated and may be different from the actual ratios.
[0021] [Composite parts]
[0022] The composite component 100 of the present embodiment includes an inorganic matrix portion 10 and a conductive material portion 20, and the conductive material portion 20 is directly bonded to the inorganic matrix portion 10 without passing through a binder different from the inorganic material constituting the inorganic matrix portion 10. Specifically, Figure 1 As shown, the composite member 100 includes an inorganic matrix portion 10 composed of an inorganic substance and a conductive material portion 20 dispersed in the inorganic matrix portion 10 .
[0023] like Figure 1 As shown, the inorganic matrix portion 10 is composed of a plurality of particles 11 formed of an inorganic substance, and the inorganic matrix portion 10 is formed by the particles 11 of the inorganic substance being bonded to each other.
[0024] The inorganic substance constituting the inorganic matrix portion 10 preferably contains at least one metal element selected from the group consisting of alkali metals, alkaline earth metals, transition metals, base metals and semimetals. In this specification, alkaline earth metals include beryllium and magnesium in addition to calcium, strontium, barium and radium. Base metals include aluminum, zinc, gallium, cadmium, indium, tin, mercury, thallium, lead, bismuth and polonium. Semimetals include boron, silicon, germanium, arsenic, antimony and tellurium. Among them, the inorganic substance preferably contains at least one metal element selected from the group consisting of aluminum, iron, nickel, gallium and yttrium.
[0025] The inorganic substance constituting the inorganic matrix part 10 contains the oxyhydroxide of the above-mentioned metal element. In addition, the inorganic substance preferably contains the oxyhydroxide of the above-mentioned metal element as a main component. That is, the inorganic substance preferably contains 50 mol% or more of the oxyhydroxide of the above-mentioned metal element, and more preferably contains 80 mol% or more of the oxyhydroxide of the above-mentioned metal element. Such an inorganic substance has high stability to oxygen and water vapor in the atmosphere, so by configuring the conductive material part 20 inside the inorganic matrix part 10, the contact between the conductive material part 20 and oxygen and water vapor can be suppressed, thereby suppressing the degradation of the conductive material part 20. It should be noted that, when the inorganic substance contains the oxyhydroxide of the above-mentioned metal element as a main component, the inorganic substance may also contain the hydroxide of the above-mentioned metal element.
[0026] In addition, the inorganic matrix part 10 is preferably a polycrystalline. That is, it is preferred that the particles 11 of the inorganic substance are crystalline particles, and the inorganic matrix part 10 is formed by agglomeration of a plurality of particles 11. By making the inorganic matrix part 10 a polycrystalline, a composite component 100 with high durability can be obtained compared to the case where it is formed by amorphous. It should be noted that the particles 11 of the inorganic substance are more preferably crystalline particles containing at least one metal element selected from the group consisting of alkali metals, alkaline earth metals, transition metals, base metals and semimetals. In addition, the particles 11 of the inorganic substance are preferably crystalline particles containing oxyhydroxides of the above-mentioned metal elements. The particles 11 of the inorganic substance are more preferably crystalline particles with the oxyhydroxides of the above-mentioned metal elements as the main component.
[0027] The metal oxyhydroxide contained in the inorganic substance of the inorganic matrix part 10 is preferably boehmite. Boehmite is an aluminum oxyhydroxide represented by the composition formula of AlOOH. Boehmite is insoluble in water and hardly reacts with acids and bases at room temperature, so it has high chemical stability, and its dehydration temperature is as high as about 500°C, so it has excellent heat resistance. In addition, the specific gravity of boehmite is about 3.07, so when the inorganic matrix part 10 is formed of boehmite, a composite component 100 with light weight and excellent chemical stability can be obtained.
[0028] In the case where the inorganic substance constituting the inorganic matrix portion 10 is boehmite, the particle 11 may be a particle formed only by the boehmite phase, or may be a particle formed by a mixed phase of boehmite and aluminum oxide or aluminum hydroxide other than boehmite. For example, the particle 11 may also be a particle formed by a phase formed by boehmite and a phase formed by gibbsite (Al(OH)3) mixed. In addition, in this case, adjacent particles 11 are preferably bonded via at least one of aluminum oxide and oxyhydroxide. That is, it is preferred that the particles 11 are not bonded via an organic binder composed of an organic compound, nor are they bonded via an inorganic binder formed by an inorganic compound other than aluminum oxide and oxyhydroxide. It should be noted that, in the case where adjacent particles 11 are bonded via at least one of aluminum oxide and oxyhydroxide, the aluminum oxide and oxyhydroxide may be crystalline or amorphous.
[0029] When the inorganic matrix portion 10 is formed of boehmite, the presence ratio of the boehmite phase is preferably 50% by mass or more, more preferably 60% by mass or more, and further preferably 70% by mass or more. By increasing the proportion of the boehmite phase, a lightweight inorganic matrix portion 10 having excellent chemical stability and heat resistance can be obtained. It should be noted that the proportion of the boehmite phase in the inorganic matrix portion 10 can be obtained by the following method: after measuring the X-ray diffraction pattern of the inorganic matrix portion 10 by X-ray diffraction, Rietveld analysis is performed.
[0030] The average particle size of the inorganic substance particles 11 constituting the inorganic matrix part 10 is not particularly limited. However, the average particle size of the particles 11 is preferably 300 nm or more and 50 μm or less, more preferably 300 nm or more and 30 μm or less, further preferably 300 nm or more and 10 μm or less, and particularly preferably 300 nm or more and 5 μm or less. By setting the average particle size of the inorganic substance particles 11 within this range, the particles 11 are firmly bonded to each other, and the strength of the inorganic matrix part 10 can be improved. In addition, by setting the average particle size of the inorganic substance particles 11 within this range, as described later, the proportion of pores present in the inorganic matrix part 10 is 20% or less, so the deterioration of the conductive material part 20 can be suppressed. It should be noted that in this specification, as the value of "average particle size", unless otherwise specified, the following value is used: a value calculated as the average value of the particle size of particles observed in several to several tens of visual fields using an observation means such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM).
[0031] The shape of the particle 11 of the inorganic substance is not particularly limited, and can be, for example, spherical. In addition, the particle 11 can also be a whisker-shaped (needle-shaped) particle or a scaly particle. Compared with spherical particles, the contact between the whisker-shaped particles and the scaly particles is improved, and the strength of the inorganic matrix part 10 is easily improved. Therefore, by using particles of such a shape as the particle 11, the overall strength of the composite component 100 can be improved.
[0032] As described above, the inorganic substance constituting the inorganic matrix portion 10 preferably contains a metal oxyhydroxide as a main component. Therefore, the inorganic matrix portion 10 also preferably contains a metal oxyhydroxide as a main component. That is, the inorganic matrix portion 10 preferably contains 50 mol % or more of the metal oxyhydroxide, and more preferably contains 80 mol % or more of the metal oxyhydroxide.
[0033] It should be noted that the inorganic substance constituting the inorganic matrix portion 10 preferably does not substantially contain a hydrate. In this specification, "the inorganic substance does not substantially contain a hydrate" means that a hydrate is not intentionally contained in the inorganic substance. Therefore, when a hydrate is mixed into the inorganic substance as an inevitable impurity, the condition of "the inorganic substance does not substantially contain a hydrate" is satisfied. It should be noted that boehmite is a metal hydroxide oxide, so it is not included in the hydrate in this specification.
[0034] In addition, the inorganic substance constituting the inorganic matrix part 10 preferably does not contain a hydrate of a calcium compound. The calcium compound referred to here is tricalcium silicate (alite, 3CaO·SiO2), dicalcium silicate (belite, 2CaO·SiO2), calcium aluminate (3CaO·Al2O3), calcium aluminoferrite (4CaO·Al2O3·Fe2O3), and calcium sulfate (CaSO4·2H2O). In the case where the inorganic substance constituting the inorganic matrix part 10 contains a hydrate of the above-mentioned calcium compound, the porosity of the cross section of the inorganic matrix part of the obtained composite component may exceed 20%. Therefore, the inorganic substance preferably does not contain a hydrate of the above-mentioned calcium compound. In addition, the inorganic substance constituting the inorganic matrix part 10 preferably does not contain phosphate cement, zinc phosphate cement, and calcium phosphate cement. By making the inorganic substance not contain these cements, the porosity of the obtained composite component can be made less than 20%.
[0035] The composite component 100 includes a conductive material portion 20 made of a conductive material. The conductive material portion 20 is dispersed inside the inorganic matrix portion 10 and is directly in contact with and fixed to the inorganic matrix portion 10. In addition, by dispersing the conductive material portion 20 having conductivity inside the inorganic matrix portion 10, the composite component 100 can exhibit conductivity. That is, by dispersing the conductive material portion 20 in the inorganic matrix portion 10, a conductive path for conducting electrons is formed inside the inorganic matrix portion 10, thereby improving the conductivity of the composite component 100.
[0036] The material constituting the conductive material portion 20 is not particularly limited as long as it has conductivity. The material constituting the conductive material portion 20 is preferably at least one selected from the group consisting of metals, carbon materials, metal oxides, metal nitrides, metal carbides, and organic compounds. As described later, the composite component 100 can be obtained by a low-temperature sintering method in which heating is performed at a low temperature of 300°C or less. Therefore, even a conductive material with low heat resistance such as an organic compound can be used as a material constituting the conductive material portion 20. In addition, in the low-temperature sintering method, since the heating temperature is low, the material constituting the conductive material portion 20 is difficult to undergo an oxidation reaction. Therefore, the composite component 100 can be manufactured in the atmosphere instead of in an inert atmosphere.
[0037] The conductive material part 20 is preferably made of metal. The metal constituting the conductive material part 20 can be, for example, at least one metal element selected from the group consisting of gold, silver, copper, platinum, iridium, palladium, ruthenium, rhodium, titanium, aluminum, tantalum, niobium, tungsten, molybdenum, vanadium, magnesium, chromium, iron, cobalt, nickel, zinc, tin and lead. The metal constituting the conductive material part 20 may be a single metal element or an alloy in which the metal elements are arbitrarily combined.
[0038] The conductive material portion 20 is preferably made of a carbon material. The carbon material constituting the conductive material portion 20 is preferably at least one selected from the group consisting of, for example, carbon black, graphite, carbon fiber, carbon nanotube, and conductive diamond.
[0039] The conductive material portion 20 is preferably composed of at least one selected from the group consisting of metal oxides, metal nitrides, and metal carbides. The metal oxide constituting the conductive material portion 20 is preferably, for example, at least one selected from the group consisting of tin-doped indium oxide (ITO), zinc-doped indium oxide (IZO), antimony-doped tin oxide, fluorine-doped tin oxide (FTO), aluminum-doped zinc oxide (AZO), and gallium-doped zinc oxide (GZO). The metal nitride constituting the conductive material portion 20 is preferably, for example, at least one selected from the group consisting of titanium nitride, zirconium nitride, tantalum nitride, vanadium nitride, chromium nitride, molybdenum nitride, and tungsten nitride. The metal carbide constituting the conductive material portion 20 is preferably, for example, at least one selected from the group consisting of titanium carbide, zirconium carbide, niobium carbide, tantalum carbide, vanadium carbide, chromium carbide, molybdenum carbide, and tungsten carbide.
[0040] The conductive material part is preferably composed of a conductive organic compound. The organic compound constituting the conductive material part 20 can be, for example, a conductive polymer. As the conductive polymer, it is preferably selected from the group consisting of polyacetylene, polydiacetylene, and polyalkyne as linear conjugated polymers; polyphenylene, polynaphthalene, polyfluorene, polyanthracene, polypyrene, and polyazulene as aromatic conjugated polymers; polypyrrole, polythiophene, polyfuran, polyselenophene, polyisothiophene, and polyoxadiazole as heterocyclic conjugated polymers; polyaniline and polythiazole as heteroatom-containing conjugated polymers; polyphenylene vinylene and polythiophenylene vinylene as mixed conjugated polymers; and polyphenylene, polyphenanthrene, and polypernaphthalene as ladder-shaped conjugated polymers. It should be noted that as the conductive polymer, poly(3,4-ethylenedioxythiophene) (PEDOT:PSS) doped with poly(4-styrenesulfonic acid) is also preferred. In addition, the conductive organic compound is preferably a conductive metal paste in which metal particles are dispersed in a polymer.
[0041] The shape of the conductive material part 20 is not particularly limited, and can be, for example, spherical, scaly, needle-shaped, or fibrous. However, the shape of the conductive material part 20 is preferably needle-shaped or fibrous. In this case, since a plurality of conductive material parts 20 are easily in contact with each other, it is easy to form a conductive path inside the inorganic matrix part 10. Therefore, the electron conduction path inside the inorganic matrix part 10 is increased, and the conductivity of the composite component 100 can be improved.
[0042] It should be noted that when the amount of the conductive material portion 20 in the inorganic matrix portion 10 exceeds a threshold value called a percolation concentration, the conductivity of the composite component 100 is greatly improved. In addition, the percolation concentration varies depending on the shape of the conductive material portion 20. Therefore, when the shape of the conductive material portion 20 is needle-shaped or fibrous, or the particle size of the conductive material portion 20 is large, there is a tendency for the threshold value to be lowered.
[0043] When the conductive material portion 20 is needle-shaped or fibrous, the aspect ratio of the conductive material portion 20 is preferably greater than 5. As a result, a plurality of conductive material portions 20 are more easily contacted, and thus a plurality of conductive paths can be formed inside the inorganic matrix portion 10. It should be noted that the aspect ratio is the ratio of the length to the diameter of the conductive material portion 20 (length / diameter), and the length and diameter of the conductive material portion 20 can be obtained by observing the cross section of the composite component 100 with a microscope.
[0044] As described above, the composite component 100 of the present embodiment is provided with a conductive material portion 20 formed of a conductive material inside the inorganic matrix portion 10. In addition, the inorganic matrix portion 10 is composed of an inorganic substance containing a metal oxyhydroxide. The metal oxyhydroxide has high stability to oxygen and water vapor in the atmosphere, so when the inorganic substance of the inorganic matrix portion 10 is formed of a metal oxyhydroxide, the oxygen permeability of the inorganic matrix portion 10 is reduced and the gas barrier property is improved. As a result, the contact between the conductive material portion 20 and oxygen and water vapor can be suppressed, thereby suppressing the degradation of the conductive material portion 20. In addition, the composite component 100 has a conductive path from the conductive material portion 20 formed inside the inorganic matrix portion 10, so that conductivity can be exerted.
[0045] It should be noted that, inside the inorganic matrix part 10, the conductive material part 20 may also be Figure 1 However, in order to facilitate the formation of a conductive path in the inorganic matrix part 10, it is preferred that the conductive material parts 20 are in contact with each other and connected. Thus, the conductive path is increased in the inorganic matrix part 10, and thus the conductivity of the composite component 100 can be further improved.
[0046] Here, in the inorganic matrix part 10 of the composite member 100, it is preferred that the particles 11 of the inorganic substance exist continuously. Figure 1 As shown, in the inorganic matrix part 10, the particles 11 of the inorganic substance are preferably in contact and connected with each other. In addition, it is preferred that the entire surface of the conductive material part 20 is covered with the inorganic matrix part 10. Thereby, the contact of the conductive material part 20 with oxygen and water vapor can be further suppressed, so that the oxidative degradation of the conductive material part 20 can be further suppressed.
[0047] In the composite component 100, the volume ratio of the inorganic matrix part 10 is preferably larger than the volume ratio of the conductive material part 20. In the composite component 100, by making the volume of the inorganic matrix part 10 larger than the volume of the conductive material part 20, it becomes easy to cover the periphery of the conductive material part 20 with the inorganic substance particles 11. Therefore, from the viewpoint of further suppressing the deterioration of the conductive material part 20, the volume ratio of the inorganic matrix part 10 is preferably larger than the volume ratio of the conductive material part 20.
[0048] In the composite component 100, the porosity of the cross section of the inorganic matrix part 10 is preferably 20% or less. That is, when observing the cross section of the inorganic matrix part 10, the average value of the pore ratio per unit area is preferably 20% or less. When the porosity is 20% or less, the conductive material part 20 can be sealed inside the dense inorganic substance. Therefore, the contact rate between oxygen and water vapor from the outside of the composite component 100 and the conductive material part 20 is reduced, so the oxidation of the conductive material part 20 can be suppressed, and the conductivity of the conductive material part 20 can be maintained for a long time. In addition, in this case, since there are fewer pores inside the inorganic matrix part 10 and the inorganic substance becomes dense, the composite component 100 can have high strength. It should be noted that the porosity of the cross section of the inorganic matrix part 10 is preferably 15% or less, more preferably 10% or less, and further preferably 5% or less. As the porosity of the cross section of the inorganic matrix portion 10 decreases, the contact between the conductive material portion 20 and oxygen and water vapor is suppressed, and thus degradation of the conductive material portion 20 can be prevented.
[0049] In this specification, porosity can be obtained in the following manner. First, observe the cross section of the inorganic matrix portion 10, and distinguish the inorganic matrix portion 10, the conductive material portion 20 and the pores. Then, measure the unit area and the area of the pores in the unit area, and find the ratio of the pores per unit area. After finding the ratio of such pores per unit area at multiple locations, the average value of the ratio of the pores per unit area is used as the porosity. It should be noted that when observing the cross section of the inorganic matrix portion 10, an optical microscope, a scanning electron microscope (SEM) or a transmission electron microscope (TEM) can be used. In addition, the unit area and the area of the pores in the unit area can also be measured by binarizing the image observed with a microscope.
[0050] It should be noted that the shape of the composite component 100 is not particularly limited, and can be set to a plate shape, for example. In addition, the thickness t of the composite component 100 is not particularly limited, and can be set to 50 μm or more, for example. As described later, the composite component 100 is formed by a pressurization and heating method, so a composite component 100 with a large thickness can be easily obtained. It should be noted that the thickness t of the composite component 100 can be set to 1 mm or more, and can also be set to 1 cm or more. The upper limit of the thickness t of the composite component 100 is not particularly limited, and can be set to 50 cm, for example.
[0051] Thus, the composite component 100 of the present embodiment comprises: an inorganic matrix part 10, which is composed of an inorganic substance containing a metal oxyhydroxide; and a conductive material part 20, which exists in a state dispersed inside the inorganic matrix part 10 and has conductivity. In addition, the porosity of the cross section of the inorganic matrix part 10 is 20% or less. In the composite component 100, the conductive material part 20 is arranged inside the inorganic matrix part 10. Therefore, the inorganic matrix part 10 suppresses the contact of the conductive material part 20 with oxygen and water vapor, so that the deterioration of the conductive material part 20 can be suppressed, and the conductivity can be exerted for a long time. In addition, as described later, the composite component 100 can be obtained by a low-temperature sintering method, so a conductive material with low heat resistance such as a conductive polymer can be used as the conductive material part 20. In addition, the metal oxyhydroxide has a smaller specific gravity than an oxide, so a lightweight composite component 100 can be obtained.
[0052] In addition, since the composite component 100 is conductive, electrostatic dirt such as dust is difficult to adhere to. That is, since the composite component 100 has a conductive path formed inside from the conductive material part 20, it is possible to suppress the charging of the composite component 100 and make it difficult for electrostatic dirt to adhere to it. Therefore, as described later, by using the composite component 100 for building components such as exterior wall components, it is possible to suppress the adhesion of electrostatic dirt and maintain a beautiful appearance for a long time.
[0053] [Method for manufacturing composite parts]
[0054] Next, the manufacturing method of the composite component involved in this embodiment is described. The composite component 100 can be manufactured by heating a mixture of precursor particles of an inorganic substance constituting the inorganic matrix part 10 and a conductive material constituting the conductive material part 20 while pressurizing in a state containing a solvent. By using such a pressurizing and heating method, the precursor particles of the inorganic substance react with the solvent, so that the particles are bonded to each other, thereby forming an inorganic matrix part 10 in which the conductive material part 20 is dispersed.
[0055] Specifically, first, a mixture is prepared by mixing a powder of a precursor of an inorganic substance constituting the inorganic matrix portion 10 and a conductive material constituting the conductive material portion 20. The powder of the inorganic substance precursor and the conductive material may be mixed in air or in an inert atmosphere. As a precursor of the inorganic substance constituting the inorganic matrix portion 10, a metal oxyhydroxide is generated by heating and pressurizing with a solvent. For example, when the inorganic substance constituting the inorganic matrix portion 10 is boehmite, hydraulic alumina may be used as a precursor of the inorganic substance.
[0056] Next, a solvent is added to the mixture. As the solvent, a solvent that reacts with an inorganic substance precursor to generate a metal oxyhydroxide is used. As such a solvent, at least one selected from the group consisting of water, an acidic aqueous solution, an alkaline aqueous solution, an alcohol, a ketone, and an ester can be used. As an acidic aqueous solution, an aqueous solution with a pH of 1 to 3 can be used. As an alkaline aqueous solution, an aqueous solution with a pH of 10 to 14 can be used. As an acidic aqueous solution, an aqueous solution of an organic acid is preferably used. In addition, as an alcohol, an alcohol with a carbon number of 1 to 12 is preferably used.
[0057] Next, a mixture containing an inorganic substance precursor, a conductive material and a solvent is filled into the inside of the mold. After the mixture is filled into the mold, the mold can also be heated as needed. In addition, by applying pressure to the mixture inside the mold, the inside of the mold becomes a high pressure state. At this time, the inorganic substance precursor and the conductive material are densified, and the particles of the inorganic substance precursor are combined with each other, and at the same time, the inorganic substance precursor reacts with the solvent to become a metal hydroxide oxide. As a result, the conductive material part 20 can be dispersed in the inside of the inorganic matrix part 10 composed of the metal hydroxide oxide.
[0058] Regarding the heating and pressurizing conditions of the mixture containing an inorganic substance, a conductive material and a solvent, there are no particular limitations as long as the solvent reacts with the inorganic substance precursor to generate a metal hydroxide oxide. For example, it is preferred that the mixture containing an inorganic substance precursor, a conductive material and a solvent is heated to 50 to 300° C. and then pressurized at a pressure of 10 to 600 MPa. It should be noted that the temperature when heating the mixture containing an inorganic substance, a conductive material and a solvent is more preferably 80 to 250° C., and further preferably 100 to 200° C. In addition, the pressure when pressurizing the mixture containing an inorganic substance, a conductive material and a solvent is more preferably 50 to 600 MPa, and further preferably 200 to 600 MPa.
[0059] Then, by taking out the molded body from the inside of the mold, the composite member 100 can be obtained.
[0060] Here, the manufacturing method of the composite component 100 in which the inorganic substance constituting the inorganic matrix part 10 is boehmite is described. The composite component 100 in which the inorganic substance is boehmite can be manufactured by mixing hydraulic alumina as a precursor of the inorganic substance, the conductive material constituting the conductive material part 20 and a solvent containing water, and then pressurizing and heating. Hydraulic alumina is an oxide obtained by heat-treating aluminum hydroxide, and contains ρ alumina. Such hydraulic alumina has the property of combining and solidifying through a hydration reaction. Therefore, by using a pressurized heating method, the hydration reaction of the hydraulic alumina is carried out, and the hydraulic alumina is combined with each other, and at the same time, the crystal structure in the boehmite changes, thereby forming the inorganic matrix part 10.
[0061] Specifically, first, a mixture is prepared by mixing powder of hydraulic alumina, a conductive material constituting the conductive material part 20, and a solvent containing water. The solvent containing water is preferably pure water or ion-exchanged water. However, the solvent containing water may contain an acidic substance or an alkaline substance in addition to water. In addition, the solvent containing water may contain water as a main component, and may contain an organic solvent (e.g., alcohol, etc.).
[0062] The amount of the solvent added to the hydraulic alumina is preferably an amount that allows the hydration reaction of the hydraulic alumina to proceed sufficiently. The amount of the solvent added is preferably 20 to 200% by mass, more preferably 50 to 150% by mass, relative to the hydraulic alumina.
[0063] Next, a mixture of hydraulic alumina, a conductive material and a solvent containing water is filled into the interior of the mold. After the mixture is filled into the mold, the mold can also be heated as needed. Then, by applying pressure to the mixture inside the mold, the interior of the mold becomes a high-pressure state. At this time, the hydraulic alumina is highly filled, and the particles of the hydraulic alumina are combined with each other, thereby achieving high density. Specifically, by adding water to the hydraulic alumina, the hydraulic alumina undergoes a hydration reaction, and boehmite and aluminum hydroxide are generated on the surface of the hydraulic alumina particles. Then, by heating and pressurizing the mixture inside the mold, the generated boehmite and aluminum hydroxide diffuse mutually between adjacent hydraulic alumina particles, and the hydraulic alumina particles gradually combine with each other. Thereafter, a dehydration reaction is carried out by heating, whereby the crystal structure changes from aluminum hydroxide to boehmite. It should be noted that it is presumed that such a hydration reaction of hydraulic alumina, the mutual diffusion between hydraulic alumina particles, and the dehydration reaction are carried out approximately simultaneously.
[0064] Then, by taking out the molded body from the inside of the mold, it is possible to obtain the composite member 100 in which the plurality of particles 11 are bonded to each other via at least one of aluminum oxide and oxyhydroxide.
[0065] In this way, the manufacturing method of the composite component 100 has the following steps: a precursor of an inorganic substance constituting the inorganic matrix part 10, a conductive material constituting the conductive material part 20, and a solvent for reacting with the inorganic substance precursor to generate a metal hydroxide oxide are mixed to obtain a mixture. The manufacturing method of the composite component 100 also has the steps of pressurizing and heating the mixture. In addition, the heating and pressurizing conditions of the mixture are preferably set to a temperature of 50 to 300° C. and a pressure of 10 to 600 MPa. In the manufacturing method of this embodiment, since the composite component 100 is molded under such low temperature conditions, the deterioration of the conductive material constituting the conductive material part 20 can be suppressed, and a composite component 100 with conductivity can be obtained.
[0066] Here, as a method for manufacturing an inorganic component formed of ceramics, a sintering method is known in the past. The sintering method is a method for obtaining a sintered body by heating an aggregate of solid powders formed of an inorganic substance at a temperature lower than the melting point. However, in the sintering method, for example, the solid powder is heated to above 1000°C. Therefore, even if you want to use the sintering method to obtain a composite component formed of an inorganic substance and a conductive organic compound, since the conductive organic compound is carbonized due to heating at a high temperature, a composite component cannot be obtained. However, in the manufacturing method of the composite component 100 of the present embodiment, since the mixture formed by mixing the precursor of the inorganic substance, the conductive material and the solvent is heated at a low temperature below 300°C, it is not easy to cause the deterioration of the conductive material. Therefore, the conductive material part 20 can be stably dispersed in the interior of the inorganic matrix part 10 to impart conductivity.
[0067] In addition, for example, when a conductive ceramic component is obtained by using metal aluminum as a conductive material, in the conventional sintering method, since the metal aluminum is heated at a high temperature, the surface of the aluminum is oxidized when an inert atmosphere is not used. Therefore, there is a problem that the conductivity of the obtained ceramic component cannot be sufficiently improved. However, in the manufacturing method of the composite component 100 of the present embodiment, since heating is performed at a low temperature of 300° C. or less, even when metal aluminum is used as a conductive material, oxidation of aluminum can be suppressed, thereby improving the conductivity of the composite component 100.
[0068] In addition, in the manufacturing method of this embodiment, since the mixture formed by mixing the inorganic substance precursor, the conductive material and the solvent is heated and pressurized, the inorganic substance is agglomerated to form a dense inorganic matrix part 10. As a result, the pores inside the inorganic matrix part 10 are reduced, so that the oxidative degradation of the conductive material part 20 can be suppressed and the composite component 100 with high strength can be obtained.
[0069] [Applications of composite parts]
[0070] Next, the purpose of the composite component 100 involved in this embodiment is described. As described above, the composite component 100 has conductivity, high mechanical strength, and can be formed into a plate-like shape with a large thickness, so it can be used for structures. In addition, as a structure having the composite component 100, residential equipment, residential components, building materials, and buildings are preferred. Residential equipment, residential components, building materials, and buildings are structures that are in high demand in people's lives, so by using the composite component 100 for structures, a new large market creation effect can be expected. In addition, the composite component 100 has conductivity, and electrostatic dirt such as dust is difficult to adhere to, so by using the composite component 100 for structures, a beautiful appearance can be maintained for a long time.
[0071] The composite component 100 of this embodiment can be used as a building component. A building component is a component manufactured for construction purposes. In this embodiment, at least a part of it can use the composite component 100. As described above, the composite component 100 can be formed into a plate-like shape with a large thickness, and has higher strength and durability. Therefore, the composite component 100 can be appropriately used as a building component. As building components, for example, exterior wall materials (exterior wall panels), roofing materials, etc. can be listed. In addition, as building components, road materials and exterior ditch materials can also be listed.
[0072] Furthermore, the composite member 100 of the present embodiment can also be used for interior parts. Examples of interior parts include bathtubs, kitchen counters, washstands, and floor materials.
[0073] It should be noted that the composite component 100 of this embodiment can also be used for purposes other than the above-mentioned building components or interior components. Specifically, the composite component 100 can also be used for semiconductor holders, electrostatic chucks, heat dissipation components, ceramic heaters, sliding components, electromagnetic wave shielding components, ceramic sensors, etc.
[0074] Example
[0075] Hereinafter, the composite component of the present embodiment will be described in more detail with reference to Examples, but the present embodiment is not limited thereto.
[0076] [Preparation of test samples]
[0077] (Example 1)
[0078] First, as hydraulic alumina, hydraulic alumina BK-112 manufactured by Sumitomo Chemical Co., Ltd. was prepared. The median particle size of the hydraulic alumina was 16 μm. Also, as metal powder, copper powder manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. was prepared.
[0079] Here, Figure 2The X-ray diffraction pattern of the hydraulic alumina powder and the patterns of boehmite (AlOOH) and gibbsite (Al(OH)3) registered in ICSD are shown in FIG. Figure 2 As shown, it can be seen that hydraulic alumina is a mixture of boehmite and gibbsite. Figure 2 Although not shown, ρ-alumina is also contained in hydraulic alumina.
[0080] Then, copper powder was weighed so as to account for 15% by volume of the hydraulic alumina, and the hydraulic alumina and copper powder were mixed using an agate mortar and pestle to obtain a mixed powder. Next, ion exchange water was weighed so as to account for 80% by mass of the hydraulic alumina, and the mixed powder and ion exchange water were mixed using an agate mortar and pestle to obtain a mixture.
[0081] Next, the obtained mixture was put into a cylindrical molding die (Φ10) having an internal space, and then the mixture was heated and pressurized under the conditions of 400 MPa, 180° C., and 20 minutes to obtain a test sample of this example.
[0082] (Example 2)
[0083] A test sample of this example was obtained in the same manner as in Example 1 except that copper powder was added so as to account for 25% by volume relative to hydraulic alumina.
[0084] (Example 3)
[0085] First, aluminum powder (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was prepared as metal powder, and a test sample of this example was obtained in the same manner as in Example 1 except that aluminum powder was used instead of copper powder and aluminum powder was further added to 19 volume % relative to hydraulic alumina.
[0086] (Example 4)
[0087] A test sample of this example was obtained in the same manner as in Example 3 except that aluminum powder was added so as to account for 31% by volume relative to hydraulic alumina.
[0088] (Example 5)
[0089] A test sample of this example was obtained in the same manner as in Example 3 except that aluminum powder was added so as to account for 48% by volume relative to hydraulic alumina.
[0090] (Comparative Example)
[0091] A test sample of this example was obtained in the same manner as in Example 1 except that the copper powder was not added.
[0092] Table 1 shows the volume ratios of the copper particles and the aluminum particles, the pressing pressure, and the pressing temperature of the test samples obtained in Examples 1 to 5 and Comparative Examples.
[0093] [Table 1]
[0094]
[0095] (Reference example)
[0096] After weighing ion exchange water in the same manner as in Example 1 so as to be 80% by mass relative to the hydraulic alumina, the hydraulic alumina and the ion exchange water were mixed using an agate mortar and pestle to obtain a mixture. Next, the obtained mixture was put into a cylindrical molding die (Φ10) having an internal space. Then, the mixture was heated and pressurized under the conditions of 50 MPa, 120° C., and 20 minutes to obtain a test sample of this example.
[0097] [evaluate]
[0098] (Volume resistivity measurement)
[0099] The volume resistivity of each test sample of Examples 1 to 5 and Comparative Example was measured. Figure 3 As shown, a cylindrical test sample 200 is clamped between two aluminum foils 201. At this time, the aluminum foil 201 is in contact with the entire upper surface and the bottom surface of the test sample 200. Then, after the resistance value between the two aluminum foils is measured by the measuring device 202, the volume resistivity of each test sample is measured according to Mathematical Formula 1. It should be noted that the measuring device 202 measures the resistance value by a two-terminal method. In addition, the "surface area of the test sample" in Mathematical Formula 1 is the area of the upper surface or the bottom surface of the test sample.
[0100] [Mathematical formula 1]
[0101] [Volume resistivity (Ω·m)] = [Resistance value (Ω)] × [Surface area of test sample (m 2 )
[0102] [Thickness of test sample (m)]
[0103] The volume resistivity of each test sample of Examples 1 to 5 and Comparative Example is shown in Table 1. Figure 4 The relationship between the volume resistivity and the volume ratio of the metal particles of the test samples of Examples 1 to 5 and Comparative Example is shown in FIG.
[0104] As shown in Table 1 and Figure 4As shown, the volume resistivity of the test samples of Examples 1 to 5 is reduced compared to the test samples of the comparative example without the conductive material part, showing conductivity. In addition, it can be seen that the volume resistivity decreases with the increase of the conductive material part. It should be noted that, by comparing Examples 1 to 2 and Examples 3 to 5, it can be seen that the test samples of Examples 1 to 2 using copper have a reduced volume resistivity despite a small volume ratio of metal particles. It is presumed that this is because the volume resistivity of copper is approximately 1.7×10 -8 Ω·m, the volume resistivity of aluminum is about 2.8×10 -8 Ω·m, so the volume resistivity of copper is low.
[0105] (Cross-section observation)
[0106] A scanning electron microscope was used to observe the cross section of the test sample of Example 2. Specifically, first, a cross-section polishing process was performed on the cross section of the cylindrical test sample of Example 2. Next, the cross section of the test sample was observed at a magnification of 3000 times using a scanning electron microscope. Figure 5 (a) is a secondary electron image of the cross section of the test sample, and (b) is a reflected electron image of the cross section of the test sample. Figure 5 As shown, the inorganic matrix part 10 formed of boehmite exists in a directly fixed manner around the conductive material part 20 formed of copper, and the entire periphery of the conductive material part 20 is covered with the inorganic matrix part 10. Therefore, it can be seen that the inorganic matrix part 10 can prevent the conductive material part 20 from being oxidatively degraded by contact with the atmosphere and water vapor.
[0107] (Porosity measurement)
[0108] The porosity of the test sample of Example 1 was measured as follows. First, the cross section of the cylindrical test sample of Example 1 was subjected to cross-section polishing. Then, a secondary electron image of the cross section of the test sample was observed at 5000 times and 20000 times using a scanning electron microscope. Figure 6 (a) is a secondary electron image showing the result of observation at a magnification of 5000 times, Figure 7 (a) is a secondary electron image showing the result of observation at a magnification of 20,000 times.
[0109] Then, by respectively Figure 6 (a) and Figure 7 The secondary electron image (a) is binarized to identify the pores. Figure 6 (a) and Figure 7 The secondary electron images of (a) are binarized as follows: Figure 6 (b) and Figure 7Then, the area ratio of the pores is calculated from the binary image, and the average value is taken as the porosity. Figure 6 (b), the area ratio of the pores is 15.9%. Figure 7 (b), the area ratio of the pores is 11.9%. Therefore, the porosity of the test sample of Example 1 is Figure 6 (b) and Figure 7 The average value of the area ratio of the pore portion in (b) is 13.9%.
[0110] Similarly, the porosity of the test sample of Example 2 was measured as follows. First, the cross-section of the cylindrical test sample of Example 2 was subjected to cross-section polishing. Then, a secondary electron image of the cross-section of the test sample was observed at 5000 times and 20000 times using a scanning electron microscope. Figure 8 (a) is a secondary electron image showing the result of observation at a magnification of 5000 times, Fig. 9 (a) is a secondary electron image showing the result of observation at a magnification of 20,000 times.
[0111] Then, by respectively Figure 8 (a) and Fig. 9 The secondary electron image (a) is binarized to identify the pores. Figure 8 (a) and Fig. 9 The secondary electron images of (a) are binarized as follows: Figure 8 (b) and Fig. 9 Then, the area ratio of the pores is calculated from the binary image, and the average value is taken as the porosity. Figure 8 (b), the area ratio of the pores is 4.1%, according to Fig. 9 (b), the area ratio of the pores is 1.7%. Therefore, the porosity of the test sample of Example 2 is Figure 8 (b) and Fig. 9 The average value of the area ratio of the pore portion in (b) is 2.9%.
[0112] according to Figure 6 to Figure 9 It can be seen that the porosity of the test samples of Example 1 and Example 2 is less than 15%, so the contact of the conductive material part 20 with the air and water vapor is suppressed, and oxidative degradation is suppressed.
[0113] (X-ray diffraction measurement)
[0114] For the test sample of the reference example, an X-ray diffraction pattern was measured using an X-ray diffraction apparatus. Fig.10, and the X-ray diffraction patterns of the test samples of the reference examples and the X-ray diffraction patterns of boehmite and gibbsite registered in ICSD are shown. Fig.10 It can be seen that the test sample of the reference example is a structure mainly composed of boehmite. Figure 2 as well as Fig.10 As shown in the figure, it can be seen that the raw material gibbsite (aluminum hydroxide) is converted into boehmite by the low-temperature sintering method.
[0115] As mentioned above, although the content of this embodiment was demonstrated based on an Example, this embodiment is not limited to these descriptions, and it is obvious that a person skilled in the art can make various deformation|transformation and improvement.
[0116] The entire contents of Tokugan 2019-197081 (filing date: October 30, 2019) are incorporated herein by reference.
[0117] Industrial Applicability
[0118] According to the present disclosure, it is possible to provide a composite component which does not require sintering in a high temperature and in an inert atmosphere during production and which can impart conductivity even when a conductive material with low heat resistance is used.
[0119] Description of Reference Numerals
[0120] 10 Inorganic matrix
[0121] 11 Particles of inorganic substances
[0122] 20 Conductive Materials Department
[0123] 100 Composite parts.
Claims
1. A composite component comprising: an inorganic matrix portion composed of an inorganic substance containing 50 mol % or more of a metal oxyhydroxide; and a conductive material portion which is dispersed inside the inorganic matrix portion and exists in a state of being directly in contact with and solidified with the inorganic matrix portion and has conductivity, in, The entire surface of the conductive material portion is covered by the inorganic matrix portion, The porosity of the cross section of the inorganic matrix portion is 20% or less.
2. The composite component according to claim 1, wherein: The conductive material portion is made of metal.
3. The composite component according to claim 1, wherein: The conductive material portion is made of a carbon material.
4. The composite component according to claim 1, wherein The conductive material portion is composed of at least one selected from the group consisting of metal oxides, metal nitrides, and metal carbides.
5. The composite component according to claim 1, wherein The conductive material portion is composed of a conductive organic compound.
6. The composite component according to any one of claims 1 to 5, wherein: The conductive material portion has an aspect ratio of 5 or more.
7. The composite component according to any one of claims 1 to 5, wherein: The metal oxyhydroxide is boehmite.
Citation Information
Patent Citations
JP1975096720A
Laser oscillator
JP2019197081A
Conductive composite ceramic
JP2008087988A
Composite member, and construction member and decoration member using same
WO2020195182A1
Composite member, and heat generation device, building member and light emitting device, each of which uses same
WO2020195183A1